Brazilian berry extract (Myrciaria jaboticaba): A promising therapy to minimize prostatic inflammation and oxidative stress. Issue 11 (27th May 2020) - Lamas, Celina A.; Kido, Larissa A.; Hermes, Túlio A.; Nogueira‐Lima, Ellen; Minatel, Elaine; Collares‐Buzato, Carla B.; Maróstica, Mário R.; Cagnon, Valéria H. A.
Abstract: Background: Brazilian berry is a fruit popularly known as "Jaboticaba, " rich in bioactive compounds with antioxidant and anti‐inflammatory properties. Senescence and overweight are increasing worldwide and are considered risk factors to prostatic pathogenesis mainly due to oxidative and inflammatory processes induction. Thus, this study aimed to evaluate the effect of two increasing doses of the patented jaboticaba peel extract (PJE) on oxidative‐stress and inflammation in the prostate of aging or high‐fat‐fed aging mice. Methods: PJE and/or high‐fat diet (HFD) treatments started with 11‐month‐old mice and lasted 60 days. The levels or the immunoexpression of different inflammatory (nuclear factor κB [NFκB], CD3+, cyclooxygenase 2 [COX‐2], toll‐like receptor 4 [TLR4], phosphorylated signal transducers and activators of transcription 3 [pSTAT‐3], tumor necrosis factor α [TNF‐α], interleukin 6 [IL‐6], and IL‐1β) and oxidative‐stress (catalase, superoxide dismutase 2 [SOD2], glutathione reductase [GSR], reduced glutathione, and glutathione peroxidase 3 [GPx3]) related molecules were analyzed by western‐blotting, immunohistochemistry, and enzyme‐linked immunosorbent assays. Results: Both PJE doses reduced the levels of oxidative‐stress‐related molecules (GPx3, GSR, catalase), lipid peroxidation (4‐hydroxynonenal), inflammatory mediators (COX‐2, TNF‐α, and pSTAT‐3) and CD3+ T cells number, which were associated with the maintenance of the glandular morphological integrity in aging and HFD‐fed‐aging mice. Nevertheless, only the high PJE dose reduced the NFκB and TLR4 levels in aging mice; and SOD2, IL‐6, and IL‐1β levels in HFD‐aging mice. Aging itself promoted an oxidative inflammation in the prostate, interfering in the levels of the different oxidative‐stress, lipid peroxidation, and inflammatory mediators evaluated, in association with high incidence of prostate epithelial and stromal damages. The HFD intake intensified aging alterations, showing an unfavorable prostatic microenvironment prone to oxidative and inflammatory damages. Conclusions: PJE exerted a dose‐dependent effect controlling inflammation and oxidative‐stress in aging and HFD‐fed aging mice prostate. This fact contributed to prostate microenvironment balance recovery, preserving the tissue architecture of this gland. Thus, the PJE emerges as a potential therapy to prevent inflammation and oxidative stress in the prostate.